PENDEKATAN COLLABOTARIVE/ITERATIVE DALAM PROSES PENTERJEMAHAN SKALA SCRUPULOSITY - Subhan El Hafiz; Yulmaida Amir; Karina Meriem Beru Brahmana (Jurnal Ilmu Perilaku, 2025)
Indonesian researchers often use translation of a scale before conducting further studies. The process is mainly conducted by back-translation procedures. However, the procedure also has limitations to validate the result; hence, the present study aims try to do an alternative approach to translate the scale, i.e., collaborative/ iterative. By utilizing data from two studies (study 1, 99 respondents; study 2, 124 respondents) on Indonesian students studying outside Indonesia and in Indonesia, the present study uses a T-Test Independent sample to analyze it. The scale is revised of Penn Inventory of Scrupulosity (PIOS-R), which is used to recognize Obsessive-compulsive disorder symptoms with a religius theme. As expected, the results show that the scale's translation is not different from the original version; specifically, the PIOS-R score between the two versions of the scale, English and Indonesia, has no statistical difference. The translation process supports the arguments that explain the collaborative/iterative approach is able to provide a good translation.